An evaluation of the course book “New Cutting Edge-Pre Intermediate” for first year non-major students of English, Thái Nguyên University of Technology- some suggestions for adapting - Phạm, Ngọc Duy (University of Languages and International Studies, 2017)
This study is carried out to evaluate the course book New Cutting Edge Pre-Intermediate by Peter Moor and Sarah Cunningham with Jane Comyns Carr. The course book has been in use for first year non-major students of English at Thái Nguyên University of Tech (...)